Shapes of an air taylor bubble in stagnant liquids influenced by different surface tensions - Lertnuwat, Boonchai (Zielona Góra: Uniwersytet Zielonogórski)
The aim of this work is to propose an empirical model for predicting shapes of a Taylor bubble, which is a part of slug flows, under different values of the surface tension in stagnant liquids by employing numerical simulations. The k - ? turbulence model was used in the framework of finite volume method for simulating flow fields in a unit of slug flow and also the pressure distribution on a Taylor bubble surface.
Keywords: Dumitrescu-and-Taylor model; Froude number; Surface tension; Taylor bubble; turbulence